(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Fine motor skills are essential for daily activities, especially those requiring precision, such as grasping objects or writing. This review explores the role of electromyography (EMG), particularly surface EMG (sEMG), in assessing fine motor skills across various populations, including typically developing children, children with motor disabilities, young adults, and elders. These groups were selected due to their unique challenges and needs in motor skill development and rehabilitation. For instance, young children may require early intervention to address developmental delays, while individuals with motor disabilities, such as those with autism or cerebral palsy, benefit from tailored therapeutic approaches. The elderly population faces age-related motor decline, making EMG a valuable tool for maintaining or improving muscle function in this group. By capturing muscle activation patterns, EMG provides a comprehensive evaluation of muscle engagement during fine motor tasks. The paper also reviews the effectiveness of digital platforms and 3D-printed toys in fine motor training, demonstrating the potential of EMG as a tool for enhancing therapeutic interventions and refining motor assessments. Emerging technologies such as artificial intelligence and machine learning may further optimize EMG signal analysis, offering innovative solutions for both clinical and home-based motor skill training.